Modelling transpiration in holm-oak savannah: scaling up from the leaf to the tree scale - Infante, J M; Rambal, S; Joffre, R (Agricultural and Forest Meteorology, 1997)
The transpiration of oak-savannas in southern Spain was modelled by scaling-up from the leaf to the tree during a drought period. Two chlaracteristics of this ecosystem were found to facilitate the modelling procedure. The first was a near-zero decoupling coefficient between the surface and the surrounding bulk air, which simplifies the transpiration formulation. The second was that the surface conductance (g) is mainly related to the vapour pressure deficit of the air (0,). Based on both of these characteristics, the modelling procedure provides a general model of transpiration over the time scale appropriate for a drought period, from days to months. The response of g to 0, was found to follow a negative exponential function, such that beyo’nd a minimum value, g becomes independent of 0,. This implies a feedback control on g by 0,. The consequences of tbis control for transpiration were found at different levels of plant water status. This explains the plants’ adaptation to long dry periods, even though there is also continuous water loss during these periods. Such an adaptation was corroborated by a seasonal hysteresis found in the relationship between transpiration and D, as a function of the plants’ water status
Keywords: oak savannas; seasonal hysteresis; southern Spain; Transpiration; vapour pressure deficit